Examining the Impact of Human-AI Collaboration on Job Performance Through Job Satisfaction Among BPO Employees - Loquinario Eugie L; Loria Beatrice M; Lasala Sofhia M; Maduro Adrian Paul M.; Castro Khristian E.; Guballo Jayvie O (International Journal for Applied Information Management, 2026)
The purpose of this study was to measure the mediating effect of job satisfaction regarding the relationship between Diversity, Equity, and Inclusion (DEI) initiatives and job performance among employees in BPO companies working in Quezon City. The objective of this study is to determine the perception of employees about their job satisfaction and job performance in regard to DEI initiatives. A quantitative approach was taken by collecting data from 280 respondents, with an additional 30 respondents for pilot testing to prove the reliability and construct validity of the instrument. Path analysis was employed to analyze the relations among DEI initiatives, job satisfaction, and job performance. The results showed that the three variables all have a positive and statistically significant relationship. DEI initiatives had a substantial direct impact on job satisfaction and a direct influence on job performance, while job satisfaction has a notable influence on job performance. The findings confirmed that work satisfaction plays the role of mediator between DEI initiatives and job performance, suggesting that inclusive practices in the workplace increase both satisfaction and performance. BPO companies were recommended to continue improving DEI initiatives by promoting equal hiring practices, equal training benefits, and inclusive work policy provisions so that high levels of work satisfaction are fostered, together with improved performance among the employees.